(untitled) (Revista Argentina de Cirugía, 2022)
Cholangiocarcinoma is a rare neoplasm and a difficult challenge for the surgeon because of its anatomic location. Surgery remains the only curative option for perihilar cholangiocarcinoma with the best survival rates at 5 years. Portal vein invasion requires portal vein resection and its corresponding reconstruction. However, as portal vein invasion is an intraoperative finding in most cases it is important to count with options for in case vascular reconstructions are needed. We report a case of perihilar cholangiocarcinoma successfully treated with surgery with portal vein invasion identified intraoperatively.